Effects of Physical Fatigue on Cardiopulmonary Resuscitation Quality by Lifeguards: A Systematic Review and Meta-analysis - Filipe Maia (International Journal of First Aid Education)
Background: Lifeguards actively contribute to the safeguarding of human lives in aquatic environments. When attending to victims of cardiac arrest in the water, lifeguards must perform basic life support after intense physical exertion that may involve running, swimming, and towing. The purpose of this review is to assess the magnitude of the effects caused by physical fatigue on the quality of subsequent cardiopulmonary resuscitation, under simulated conditions. Methods: A systematic literature search was conducted following PRISMA guidelines, covering the databases: PubMed, Web of Science, ScienceDirect, and Academic Search Complete, using the keywords: (lifeguard) AND ("cardiopulmonary" OR "cardiorespiratory" OR "basic life support" OR "resusc*"). Articles published until 25 May 2023 were considered for inclusion.  The methodological quality of the included studies was assessed using the JBI Critical Appraisal Tool. The pooled data analysis was conducted using a random-effects model, with heterogeneity assessed using I2. Results: In total, 8 studies (297 lifeguards) were included. Results indicate that physical fatigue jeopardizes the quality of compressions (ES: -0.90) and ventilations (ES: -1.10). Conclusions: In general, lifeguards perform cardiopulmonary resuscitation poorly, especially when physically fatigued.  Hence, this underscores the importance of keeping these professionals prepared to perform basic life support.